Tasyahud Akhir (Kajian Teks Hadis Rasulullah saw.) - Fadhlina Arief Wangsa; Nurul Iqram Asdar (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2023)
Most of the verses of the Qur'an in tafshili (detail) need to be explained with hadith, such as the command to pray by looking at the hadith from the Prophet Muhammad, the pillars of prayer, one of which is sitting at the final tasyahud. This research is a library research, by collecting related literature, then it is presented in a qualitative descriptive manner, namely displaying the data as it is. Based on the hadith of the Prophet about the final tasyahud sitting provides an understanding that there are various views regarding the reading and the final tasyahud sitting position in prayer. it is obligatory during the recitation of tahiat to say salam to us and to the authentic servants of Allah. The last sitting in the prayer is done with iftirosy or Tawarruk. Various kinds of tahiat pronunciations included in the hadith can also be practiced.